IMPLEMENTASI SISTEM POIN DALAM MENINGKATKAN KEDISIPLINAN DAN AKHLAK MULIA SISWA DI MADRASAH ALIYAH DARUL FAIZIN CATAK GAYAM MOJOWARNO JOMBANG - HOSNA, ROFIATUL (Al Tadib : Jurnal Ilmu Pendidikan, 2018)
Abstract: This article aims to describe the discipline and good behaviors of students and theimplementation of points system toward discipline and behaviors in Madrasah Aliyah Darul FaizinCatak Gayam Mojowarno Jombang. With qualitative phenomenological approach, this research isdone by interview, observation, and documentation study in data collection and descriptive analysistechnique with data reduction procedure, data presentation, and verification / withdrawal ofconclusion. Result of research: Firstly, discipline and morals of students in Madrasah Aliyah DarulFaizin Catak Gayam Jombang include time discipline, discipline obey the rules, and discipline inworship. Second, the morality of the students developed in the points system is to get off the vehiclewhen entering the school environment, salutation and salim when meeting the teacher / father, doingand talking well, dressed courteously, neat appearance, praying when starting to study, cleanliness,and dhuha prayer. Third, the implementation of points system in improving the discipline and noblecharacter of the students in Madrasah Aliyah Darul Faizin Catak Gayam Jombang covers theimplementation by the head of the madrasah, the implementation by the teacher, and theimplementation by the students. The sanctions for the violating students are light sanction 1-35,medium sanction 36-50, and heavy sanction 51-100.Keywords: Point System, Discipline, Good Behavior Abstrak: Artikel ini bermaksud mendeskrispikan kedisiplinan dan akhlak siswa dan pelaksanaansistem poin di Madrasah Aliyah Darul Faizin Catak Gayam Mojowarno Jombang. Dengan pendekatankualitatif fenomenologis, penelitian ini dilakukan dengan interview, observation, dan studidokumentasi dalam pengumpulan data dan teknik analisis diskriptif dengan prosedur reduksi data,penayangan data, dan verifikasi/penarikan simpulan. Hasil penelitian: Pertama, kedisiplinan danakhlak siswa di Madrasah Aliyah Darul Faizin Catak Gayam Jombang meliputi disiplin waktu,disiplin mematuhi peraturan, dan disiplin dalam beribadah. Kedua, akhlak siswa yang dikembangkandalam sistem poin adalah turun dari kendaraan jika memasuki lingkungan madrasah, salam dan salimketika bertemu bapak/ibu guru, berbuat dan berbicara dengan baik, berbusana yang sopan, penampilanyang rapi, berdo’a ketika mulai belajar, menjaga kebersihan, dan shalat dhuha. Ketiga, pelaksanaansistem poin dalam meningkatkan kedisiplinan dan akhlak mulia siswa di Madrasah Aliyah DarulFaizin Catak Gayam Jombang meliputi pelaksanaan oleh kepala madrasah, pelaksanaan oleh guru,dan pelaksanaan oleh siswa. Adapun sanksi bagi siswa yang melanggar adalah sanksi ringan 1-35,sanksi sedang 36-50, dan sanksi berat 51-100.Kata Kunci: Sistem Poin, Kedisiplinan, Akhlak Mulia